2010
DOI: 10.1536/ihj.51.377
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term (4-Year) Outcomes and Predictors of Adverse Cardiac Events After Sirolimus-Eluting Stent Implantation in Unprotected Left Main Coronary Artery

Abstract: SummaryThe long-term safety and efficiency of sirolimus-eluting stent (SES) treatment in unprotected left main coronary artery (ULMCA) have not yet been ascertained.From 2003 to 2006, 126 consecutive patients with de novo lesions in ULMCA who underwent SES were retrospectively analyzed in a single center in China. During 4-year follow-up, major adverse cardiovascular event (MACE)-free survival was 74.6%. Cardiac death occurred in 5 (4.0%), and target lesion revascularization (TLR) and target vessel revascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…It was defined as death, non-fatal myocardial infarction, and target lesion revascularization (TLR). Target lesion revascularization 8 was defined as a new intervention (percutaneous or surgical) on a previously implanted stent, or within 5 mm of that stent. Deaths were classified as either cardiac or non-cardiac.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was defined as death, non-fatal myocardial infarction, and target lesion revascularization (TLR). Target lesion revascularization 8 was defined as a new intervention (percutaneous or surgical) on a previously implanted stent, or within 5 mm of that stent. Deaths were classified as either cardiac or non-cardiac.…”
Section: Methodsmentioning
confidence: 99%
“…Deaths that could not be classified were considered cardiac according to the Academic Research Consortium definitions. 8 Myocardial infarction 9 was diagnosed by an elevation of serum creatine kinase or troponin 3 times the upper limit of normal, together with chest pain lasting more than 30 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…In a single-centered registry of patients with lesions treated with PCI with SES, XiaFan Wu et al [21] reported an incidence of cardiac death of 4% and TLR of 1.9% at 3 years of follow-up. Impaired LVEF (<40%) 1 OPEN ACCESS Table 5.…”
Section: Discussionmentioning
confidence: 99%